Antifungal Efficacy of Sodium Hypochlorite and Four Intracanal Medicaments: An in vitro Evaluation - Kudva, Aravind; Shetty, Harish Kumar; Bhat, Sneha R; Kini, Shravan (Journal of Orofacial Research, 2014)
Objective: To evaluate the effect of 2.5% sodium hypochlorite and four intracanal medications on Candida albicans harvested inside root canals. Materials and methods: The contaminated canals were irrigated with sterile saline and then treated as follows: filled with (1) calcium hydroxide and saline, (2) calcium hydroxide and 2% chlorhexidine gluconate, (3) zinc oxide and 2% chlorhexidine gluconate, (4) amphotericin B powder and distilled water, (5) irrigation with 2.5% sodium hypochlorite with no medication and (6) no intracanal medication. Canal access and apex were sealed with cavit and the roots were stored in an incubator at 37 ± 1°C for 14 days. The canals were reinstrumented and irrigated with saline. Sterile paper points were used to transfer the root canal contents to test tubes containing saline. Part of the suspension was harvested on Sabouraud dextrose agar with chloramphenicol and incubated at 37 ± 1°C for 48 hours. Results: Group 5 was effective in 90% of the samples and least effective was group 1 (50% effective). Conclusion: Within the limitations of this study, long-term intracanal medication was important to eliminate microorganisms especially Candida albicans present inside root canal.